Labor unemployment insurance and earnings management - Dou, Yiwei; Khan, Mozaffar; Zou, Youli (Journal of Accounting and Economics, 2016)
We provide new evidence that firms appear to manage long-run earnings upward in order to manage rank and file employees’ perceptions of employment security. In particular, we exploit exogenous state-level changes in unemployment insurance benefits and test for partial unwinding of prior upward earnings management when benefits increase. Consistent with the hypothesis, we find a significant reduction in abnormal accruals, increased recognition of special items and write downs, and greater likelihood of net income-reducing restatements, following an increase in state-level unemployment benefits. A number of cross-sectional results are also consistent with the hypothesis.